Human adipose-derived stem cells promote vascularization of collagen-based scaffolds transplanted into nude mice. (April 2016) - Cherubino, Mario; Valdatta, Luigi; Balzaretti, Riccardo; Pellegatta, Igor; Rossi, Federica; Protasoni, Marina; Tedeschi, Alessandra; Accolla, Roberto S; Bernardini, Giovanni; Gornati, Rosalba
Aim: After in vivo implantation of cell-loaded devices, only the cells close to the capillaries can obtain nutrients to maintain their functions. It is known that factors secreted by stem cells, rather than stem cells themselves, are fundamental to guarantee new vascularization in the area of implant.Materials & methods: To investigate this possibility, we have grafted mice with Bilayer and Flowable Integra ® scaffolds, loaded or not with human adipose-derived stem cells.Results: Our results support the therapeutic potential of human adipose-derived stem cells to induce new vascular networks of engineered organs and tissues.Conclusion: This finding suggests that our approach can help to form new vascular networks that allow sufficient vascularization of engineered organs and tissues in cases of difficult wound healing due to ischemic conditions.